Retinol e carotenóides em pacientes hemodialisados e seus reflexos fisiopatológicos - Roehrs, Miguel (2009)
Chronic renal failure (CRF) is a slow and gradual decline of renal function and it constitutes a major public health problem in our country. The haemodialysis treatment is the standard to which these patients are submitted. Despite increasing the survival of the patient, it is unable to fully correct the metabolic disorders. This procedure has amplified oxidative stress, which is very common among patients with CRF. These disorders added to the oxidative stress are the main factors that can trigger the development of vascular diseases. And these are the main cause of morbidity and mortality in these patients. It is also important to study the nutrition condition in these patients, related to vitamins and carotenoids, since exogenous antioxidants could potentially have a protective role against vascular diseases. In this study it was quantified the blood levels of vitamin A (retinol), vitamin E (α-and γ-tocopherol), carotenoids (lycopene, lutein, zeaxanthin, β -cryptoxanthin, α-and β -carotene),biomarkers of oxidative stress, as reduced glutathione (GSH), malondialdehyde (MDA), δ-aminolevulinate dehydratase (ALA-D), glutathione peroxidase (GPx), catalase (CAT) and superoxide dismutase (SOD), and some biochemical parameters (urea, creatinine, lipid profile : total cholesterol, LDL cholesterol, HDL cholesterol and triglycerides and their relation) in patients with CRF submitted to the treatment of haemodialysis (HD) (n = 29) and a group of healthy subjects (control group, n = 20). The levels of retinol were significantly increased in haemodialysis patients. Among carotenoids, only the α- carotene and lycopene showed a significant decrease in patients. The plasma MDA and erythrocyte GSH levels and the activities of enzymes SOD and CAT were increased in HD, unlike the GPx and ALA-D that were reduced. The biochemical parameters urea and creatinine levels were increased, as observed in the parameters of the lipid profile (total cholesterol, LDL and triglycerides), already the HDL cholesterol was decreased. The total cholesterol / cholesterol HDL and LDL cholesterol / HDL cholesterol also known as coronary risk index were increased about three times in haemodialysis patients. Besides, the retinol showed negative correlation with the enzyme ALA-D and positive correlations with the MDA, SOD and CAT. The levels of lycopene had negative correlations with the MDA, LDL cholesterol and with LDL cholesterol / HDL cholesterol. The results obtained suggest that HD patients have some disorders for some vitamins, carotenoids and endogenous enzymes. Among the vitamins, the retinol appears in high concentrations and act as an oxidant agent / pro-oxidant. Among the carotenoids, the low concentrations of lycopene may represent an additional factor in atherogenesis, since it has antioxidant and hypocholesterolemic activity.